Interferon-γ and Hypoxia Priming Have Limited Effect on the miRNA Landscape of Human Mesenchymal Stromal Cells-Derived Extracellular Vesicles - Peltzer, Juliette; Lund, Kyle; Goriot, Marie-Emmanuelle; Grosbot, Marion; Lataillade, Jean-Jacques; Mauduit, Philippe; Banzet, Sébastien (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal Stromal Cell (MSC)-based cell therapy has received great interest in regenerative medicine. Priming the cells during the culture phase can improve their efficacy and/or survival after injection. The literature suggests that MSC extracellular vesicles (EV) can recapitulate a substantial part of the beneficial effects of the cells they originate from, and that miRNAs are important players in EV biological action. Here, our aim was to determine if two classical priming methods of MSC, interferon-gamma and hypoxia, could modify their EV miRNA content. Human bone marrow MSC from 5 healthy donors were cultured with interferon-Υ (IFN) or in hypoxia (HYP) or in control conditions (CONT). The conditioned media were collected after 48h in serum-free condition and EV were isolated by ultracentrifugation. Total RNA was isolated, pools of CONT, IFN and HYP cDNA were prepared and a miRNA profiling was performed using RT-qPCR. Then, miRNA were selected based on their detectability and measured on each individual EV sample. Priming had no effect on EV amount or size distribution. A set of 81 miRNAs was detected in at least one of the pools of EVs. They were measured on each individual sample, 41 miRNAs were detected in all samples. The principal component analysis failed to discriminate the groups. HYP induced a significant decrease in EV hsa-miR-34a-3p content and IFN induced a significant increase in 5 miRNAs (hsa-miR-25-3p, hsa-miR-106a-5p, hsa-miR-126-3p, hsa-miR-451a and hsa-miR-665). Taken together, we found only limited alterations in the miRNA landscape of MSC EV with a high inter-individual variability.